Subcutaneous emphysema related to air‐powder tooth polishing: a report of three cases. (16th July 2017) - Alonso, V; García‐Caballero, L; Couto, I; Diniz, M; Diz, P; Limeres, J
Abstract: Subcutaneous emphysema is a rare complication of dental procedures and can occasionally give rise to potentially life‐threatening complications. We describe three cases of subcutaneous emphysema diagnosed in the same dental clinic. All cases occurred during tooth or implant cleaning using air polishing (KavoProphyflex ® ) with a sodium bicarbonate powder (Air‐N‐Go Classic ® ). The diagnosis was based on clinical findings and was confirmed radiologically. The cervical and facial regions were affected in all three cases, and spread to the mediastinum occurred in one case. All the episodes resolved within 3–5 days. Tooth cleaning using air polishing combined with an abrasive powder is a risk factor for subcutaneous emphysema, especially when the powder and device are from different manufacturers. Radiological assessment must be performed to rule out involvement of deep tissue planes.